Exploring Life Instability's Relationship to the Mental Health of Older Adults With HIV. (17th December 2021) - Harkness, Audrey; Ironson, Gail; Shrader, Cho-Hee; Duncan, Dustin; Safren, Steven; Weinstein, Elliott
Abstract: The study is one of the first to examine both the prevalence of life instability among older adults with HIV (OAWH) in a community clinic and its relationship to their mental health. OAWH (N=623) from a community medical clinic completed an interviewer-administered assessment (English/Spanish) which included an additive Life Instability Index (LII) composed of indicators at the individual (e.g. education, housing instability, employment status) and community (e.g. poverty, transportation) levels. Participants were a mean age of 60 years (SD = 5.90) with the majority identifying as Black-non-Hispanic (65.9%), cisgender male (60.8%), and heterosexual (80.6%). Participants reported an average of 6.08 destabilizing factors (SD = 1.44). In multiple linear regression analyses LII was significantly related to increased substance use among participants (b= 0.08, p < 0.01), but not with anxiety or depression. An LII is an innovative approach to assess the relationship between OAWH's mental health and social determinants of health.